Diatom valve counts from surface sediments from Young Sound fjord, North-East Greenland - Mäkelä, Meri Marianne; Luostarinen, Tiia; Ribeiro, Sofia; Weckström, Kaarina; Sejr, Mikael K; Winding, Mie Hylstofte Sichlau; Heikkilä, Maija (In: Mäkelä, MM et al. (2025): Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982994, 2025)
Surface sediment samples collected from Young Sound fjord, Northeast Greenland, in 2013 or 2015. The surface sediment cores were collected as individual trips from small rubber boats using a Rumohr lot corer, multi corer or Kayak corer. Diatoms were counted and identified using a Zeiss Axio Imager.A2 upright research microscope with a Plan-Apochromat 100×/1.4 oil immersion objective, phase contrast optics and a total magnification of ×1000.
Keywords: Arctic; Diatom; Dinocysts; Dinoflagellate cysts; Sediment trap; Young Sound-Greenland